If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -4x(x + -3) = 17 Reorder the terms: 5x + -4x(-3 + x) = 17 5x + (-3 * -4x + x * -4x) = 17 5x + (12x + -4x2) = 17 Combine like terms: 5x + 12x = 17x 17x + -4x2 = 17 Solving 17x + -4x2 = 17 Solving for variable 'x'. Reorder the terms: -17 + 17x + -4x2 = 17 + -17 Combine like terms: 17 + -17 = 0 -17 + 17x + -4x2 = 0 Begin completing the square. Divide all terms by -4 the coefficient of the squared term: Divide each side by '-4'. 4.25 + -4.25x + x2 = 0 Move the constant term to the right: Add '-4.25' to each side of the equation. 4.25 + -4.25x + -4.25 + x2 = 0 + -4.25 Reorder the terms: 4.25 + -4.25 + -4.25x + x2 = 0 + -4.25 Combine like terms: 4.25 + -4.25 = 0.00 0.00 + -4.25x + x2 = 0 + -4.25 -4.25x + x2 = 0 + -4.25 Combine like terms: 0 + -4.25 = -4.25 -4.25x + x2 = -4.25 The x term is -4.25x. Take half its coefficient (-2.125). Square it (4.515625) and add it to both sides. Add '4.515625' to each side of the equation. -4.25x + 4.515625 + x2 = -4.25 + 4.515625 Reorder the terms: 4.515625 + -4.25x + x2 = -4.25 + 4.515625 Combine like terms: -4.25 + 4.515625 = 0.265625 4.515625 + -4.25x + x2 = 0.265625 Factor a perfect square on the left side: (x + -2.125)(x + -2.125) = 0.265625 Calculate the square root of the right side: 0.515388203 Break this problem into two subproblems by setting (x + -2.125) equal to 0.515388203 and -0.515388203.Subproblem 1
x + -2.125 = 0.515388203 Simplifying x + -2.125 = 0.515388203 Reorder the terms: -2.125 + x = 0.515388203 Solving -2.125 + x = 0.515388203 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.125' to each side of the equation. -2.125 + 2.125 + x = 0.515388203 + 2.125 Combine like terms: -2.125 + 2.125 = 0.000 0.000 + x = 0.515388203 + 2.125 x = 0.515388203 + 2.125 Combine like terms: 0.515388203 + 2.125 = 2.640388203 x = 2.640388203 Simplifying x = 2.640388203Subproblem 2
x + -2.125 = -0.515388203 Simplifying x + -2.125 = -0.515388203 Reorder the terms: -2.125 + x = -0.515388203 Solving -2.125 + x = -0.515388203 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.125' to each side of the equation. -2.125 + 2.125 + x = -0.515388203 + 2.125 Combine like terms: -2.125 + 2.125 = 0.000 0.000 + x = -0.515388203 + 2.125 x = -0.515388203 + 2.125 Combine like terms: -0.515388203 + 2.125 = 1.609611797 x = 1.609611797 Simplifying x = 1.609611797Solution
The solution to the problem is based on the solutions from the subproblems. x = {2.640388203, 1.609611797}
| -8.1=-13.4-1.4x | | 2e^6x+e^3x-28=0 | | 10x+29=6x+121 | | -9/8t=7/4 | | 2x=n(a+y) | | 4x+8x-2=20-15 | | 5(4-k)=10 | | 5-b=2x | | 16=5(x-1)-(x-9) | | (6x-6)+(5x-2)+x= | | 6(2x-2)=2(6+5) | | 6x=458.40 | | v-2.72=3.63 | | X+sqrt(x)=0 | | 14(t-6)+4t=6(3t+4)-11 | | 12/5=6x | | 3v-15=36 | | 9p-7p= | | 3(a-5)=-10 | | (1-1/n)(1-2/n) | | 0.25x^2-8x+64=0 | | 4y+4y=7y-1 | | 5(x+10)=40 | | 5(x-4)=3x-7 | | 36.90=9 | | x-3=-27 | | 9p-7p+4p-6p= | | 3x/4=9/2 | | 9y^2+54y+0=0 | | 9x+8=4x-3 | | -3=-27 | | -2(2x-4)+8x-4= |